2018
DOI: 10.1111/resp.13436
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors for the development of pulmonary disease identified by genome‐wide association

Abstract: Chronic respiratory diseases are a major cause of morbidity and mortality. Asthma and chronic obstructive pulmonary disease (COPD) combined affect over 500 million people worldwide. While environmental factors are important in disease progression, asthma and COPD have long been known to be heritable with genetic components playing an important role in the risk of developing disease. Identification of genetic variation contributing to disease progression is important for a number of reasons including identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 84 publications
(226 reference statements)
0
41
0
Order By: Relevance
“…This observation is supported by familial aggregation studies and reports of associations among polymorphisms in nitric oxide synthase (NOS) 3, glutathione s-transferase pi (GSTPI), tumour necrosis factor (TNF), interleukin-(IL)10, iron regulatory binding protein (IREB)2 and cholinergic nicotine receptor alpha3 (CHRNA3) and COPD phenotypes including lung function in AAT deficiency, suggesting that there are other genes which act as modifier genes in the condition 16,17 . Many of these genes have also been linked to COPD susceptibility in normal individuals (Table 1) 8,9,18,19 . About 1 in 30 individuals in the USA are heterozygous for mutations associated with AAT deficiency, the vast majority of which are of the PiMZ genotype.…”
Section: Single Gene Hereditary Disorders and Chronic Obstructive Pulmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is supported by familial aggregation studies and reports of associations among polymorphisms in nitric oxide synthase (NOS) 3, glutathione s-transferase pi (GSTPI), tumour necrosis factor (TNF), interleukin-(IL)10, iron regulatory binding protein (IREB)2 and cholinergic nicotine receptor alpha3 (CHRNA3) and COPD phenotypes including lung function in AAT deficiency, suggesting that there are other genes which act as modifier genes in the condition 16,17 . Many of these genes have also been linked to COPD susceptibility in normal individuals (Table 1) 8,9,18,19 . About 1 in 30 individuals in the USA are heterozygous for mutations associated with AAT deficiency, the vast majority of which are of the PiMZ genotype.…”
Section: Single Gene Hereditary Disorders and Chronic Obstructive Pulmentioning
confidence: 99%
“…Additionally, familial aggregation has been observed in COPD 6,7 , and several monogenetic conditions including alpha-1 antitrypsin (AAT) deficiency and cutis laxa are associated with the development of COPD, further supporting a role for genetic susceptibility in disease pathogenesis. Genetic linkage and candidate gene studies, genome-wide association studies (GWAS), exome and whole genome sequencing (WGS) have identified genes and loci associated with the condition 8,9 . Importantly, these studies have the potential to provide insights into COPD pathogenesis, improve risk prediction and lead to the development of new therapies for the disease and to the personalisation of COPD care 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hall et al provided a comprehensive overview of the most salient findings from large-scale genome-wide association (GWA) studies in COPD over the past decade. 33 These GWA studies have been largely powered on two phenotypes: (i) lung function parameters (and most notably FEV 1 or FEV 1 /forced vital capacity (FVC) ratio) and (ii) a clinical diagnosis of COPD. Although there is significant overlap of genome-wide 'hits' between these two phenotypes, there are genetic loci that are distinct for each.…”
Section: Emerging Areas In the Era Of 'Omics'mentioning
confidence: 99%
“…reviewed genome‐wide association studies (GWAS) that delineate populations at risk of respiratory disease. Single nucleotide polymorphisms (SNP) are common mutations in people and may be associated with disease such as ADAMTS4 and asthma …”
Section: Identifying At‐risk Populationsmentioning
confidence: 99%